High-extinction-ratio nanowire grid polarizing device and preparation method

CN122962705APending Publication Date: 2026-10-23江苏优众微纳半导体科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611460795.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-20
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0010]为解决现有技术中存在的上述问题,本发明提供了一种高消光比纳米线栅偏振器件及制备方法,解决现有技术中纳米线栅偏振器件存在的硬模刻蚀性能不足、纳米压印工艺缺陷突出、薄膜沉积质量不佳、刻蚀与清洗工艺易造成结构损伤、光学性能匹配度差以及硬模采购成本高和交付周期长等问题

Benefits of technology

本发明通过二代硅基大深度硬模(深度150nm)、Ti/Al复合功能膜层及多组分混合气体刻蚀工艺,可实现线栅深度精准控制在150~200nm区间,搭配占空比0.5的设计,使器件在400~1600nm全波段消光比满足高端设备使用指标,同时维持稳定的偏振透过率;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122962705A_ABST
    Figure CN122962705A_ABST
Patent Text Reader

Abstract

The application discloses a high-extinction-ratio nano-wire grid polarizing device, comprising a substrate, which is quartz glass; a functional film layer, which is arranged on the surface of the substrate and is a composite structure of a Ti transition layer and an Al polarizing functional layer; and a wire grid core structure, which is formed on the surface of the functional film layer. The application also discloses a preparation method of the high-extinction-ratio nano-wire grid polarizing device. Through the synergistic optimization of the composite functional film layer design, the large-depth hard mask preparation and the combined post-cleaning process, the process yield and reliability are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of micro-nano optical devices and semiconductor nanofabrication technology, specifically a high extinction ratio nanowire grid polarization device and its preparation method. Background Technology

[0002] Currently, nanowire grid polarization devices in the industry are generally fabricated using traditional photolithography + single-layer deposition + conventional dry etching processes, with the supporting hard molds mostly relying on external procurement. The grid structure uses aluminum as the polarization functional layer and silicon / quartz as the substrate, relying on the grid period, linewidth, and depth to achieve polarization and beam splitting functions. The conventional process chain is: purchased nanohard mold → electron beam evaporation deposition → nanoimprinting → single-gas etching → conventional cleaning. The typical grid design has a period of 40–400 nm, a linewidth of 20–200 nm, and a depth of 50–200 nm.

[0003] Currently, the core shortcomings of existing technologies are as follows: Insufficient hard mold etching performance: Traditional Al film etching selectivity is low, and shallow hard molds cannot directly etch deep aluminum wire grid structures; after hard mold etching, structural wire breakage and sidewall adhesion problems are prone to occur, and the service life and structural accuracy of hard molds are greatly reduced.

[0004] The nanoimprinting process has significant defects: the original imprinting adhesive is not properly matched, and the adhesion of the hard mold will cause the grid structure to break during the demolding process; when the base adhesive is too thick, the stability of the subsequent oxygen removal process is poor; the grid line width and height dimensions deviate greatly after imprinting, and the structural consistency is poor.

[0005] Poor thin film deposition quality: When preparing aluminum film layers, the film layer has poor density, and the actual film thickness after imprinting does not meet the design requirements, which directly affects the core optical indicators of the device such as polarization transmittance and extinction ratio.

[0006] Etching and cleaning processes can easily cause structural damage: Imprint adhesive has poor oxygen resistance, and conventional cleaning methods cannot completely remove the adhesive, which can easily lead to wire breakage, adhesion, and wire breakage; a single etching gas combination has weak control over the wire outline, resulting in substandard finished product structure morphology.

[0007] Poor optical performance matching: Existing technologies lack systematic simulation and optimization of the combination of parameters such as grating period, depth, and duty cycle, and the extinction ratio and polarization transmittance do not meet the standards of high-end applications; the grating angle and material ratio have not been specifically designed.

[0008] High procurement costs and long delivery cycles for hard molds: The unit price of an externally purchased 8-inch nano hard mold can reach up to 1 million yuan per piece. The total price for bulk purchases is high, and the delivery time can be as long as 3 months, resulting in strong dependence on the supply chain.

[0009] Therefore, to address the above issues, a high extinction ratio nanowire grating polarization device and its fabrication method are provided. Summary of the Invention

[0010] To address the aforementioned problems in the prior art, this invention provides a high extinction ratio nanowire grid polarization device and its fabrication method, solving the problems of insufficient hard mold etching performance, prominent defects in nanoimprinting process, poor thin film deposition quality, structural damage caused by etching and cleaning processes, poor optical performance matching, high hard mold procurement cost, and long delivery cycle in the prior art.

[0011] The technical solution to achieve the above objectives is: One of the present inventions provides a high extinction ratio nanowire grating polarization device, comprising: The substrate is made of quartz glass. Functional film layer, which is disposed on the surface of the substrate, is a composite structure of Ti transition layer and Al polarization functional layer; A wire grid core structure is formed on the surface of the functional film layer; The core structural parameters of the wire grid include: period Line width ,depth and duty cycle ; Duty cycle This is the ratio of line width to period, i.e.: .

[0012] Preferably, the thickness range of the Ti transition layer of the functional film is 4 to 10 nm, and the thickness range of the Al polarization functional layer of the functional film is 100 nm to 200 nm.

[0013] Preferably, the duty cycle of the wire grid core structure The period is 0.5. 100–110 nm, depth The wavelength is 150–200 nm.

[0014] Preferably, the incident angle of the wire grating core structure is 0±20°, and the polarization is defined as S-beam. Perpendicular to the grid, P-beam Parallel to the grid.

[0015] A method for fabricating a high extinction ratio nanowire grating polarization device according to a second aspect of the present invention includes: Step S1: Prepare a matching silicon-based hard mold, i.e., a quartz substrate; Step S2: Deposit a Ti transition layer and an Al polarization functional layer on a quartz substrate to form a composite functional film. Step S3: Coat the composite functional film layer with pure organic nanoimprint adhesive and perform nanoimprinting using a quartz substrate to transfer the grid pattern. Step S4: Dry etching is performed on the imprinted Al polarization functional layer using a multi-component mixed gas to form a wire grid core structure. Step S5: Perform combined post-cleaning on the etched grid core structure to remove residual adhesive.

[0016] Preferably, in step S1, the fabrication process of the silicon-based hard mold is as follows: A first-generation hard mold with a depth of 50 nm was prepared by dry etching with mixed gases. or, By introducing a metal mask layer and etching the metal mask layer and the dielectric layer in two steps, a second-generation deep hard model with a depth of 150nm is prepared.

[0017] Preferably, in step S2, the deposition adopts a magnetron sputtering scheme, and the film thickness and uniformity are controlled by adjusting the sputtering power, protective gas flow rate, cavity gas pressure and deposition time. or, The deposition process employed an electron beam evaporation method, sequentially depositing a Ti transition layer and an Al polarization layer. The thickness of the Ti transition layer ranged from 4 to 10 nm, while the thickness of the Al polarization layer ranged from 100 nm to 200 nm.

[0018] Preferably, in step S3, the pure organic nano-imprinting adhesive is the KSA08 series imprinting adhesive, and the appropriate dilution ratio and spin coating speed are adopted according to the specifications of the hard mold, that is: For the first-generation hard mold, the printing adhesive dilution ratio is 1:4, the uniform spraying speed is 3000rpm, and the platform temperature is room temperature, achieving a near-no-base adhesive state. For the second-generation deep hard mold, the printing adhesive dilution ratio is 1:2, the uniform coating speed is 2000 rpm, the platform temperature is room temperature, and the printing pressure is in the low load range.

[0019] Preferably, in step S4, the dry etching process distinguishes between two working conditions: conventional deep etching and extended deep etching by adjusting the radio frequency power, bias voltage, and reaction gas flow rate ratio, and matches the etching reaction time according to the target gate depth.

[0020] Preferably, in step S5, the combined post-cleaning specifically includes: First, plasma oxidation treatment is performed, followed by constant-temperature immersion in a high-temperature organic alkaline solution, and finally immersion and cleaning in a polar organic solvent.

[0021] Compared with the prior art, the beneficial effects of the present invention are: This invention utilizes a second-generation silicon-based deep hard mode (150nm depth), Ti / Al composite functional film, and multi-component mixed gas etching process to achieve precise control of the grid depth within the range of 150-200nm. Combined with a duty cycle design of 0.5, the device meets the extinction ratio requirements of high-end equipment across the entire wavelength range of 400-1600nm, while maintaining stable polarization transmittance. The core structure of the wire grid supports an incident angle range of 0±20°, and the polarization definition of S-beam perpendicular to the wire grid and P-beam parallel to the wire grid, which can adapt to the incident angle requirements of different optical systems and broaden the application scenarios of the device. It is compatible with various transparent substrates such as quartz glass, high aluminosilicate glass, and sapphire single crystal. Only by adjusting the pretreatment parameters of the film layer according to the substrate material can the adhesion and structural stability of the functional film layer be guaranteed, meeting the special requirements of different application scenarios for the substrate. Attached Figure Description

[0022] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings: Figure 1 This is a flowchart of a method for fabricating a high extinction ratio nanowire grid polarization device according to the present invention; Figure 2 This is a schematic diagram of the polarization optical path in an embodiment of the present invention; Figure 3 This is a schematic diagram of the full-band spectrum of the nanowire grid polarization device prepared according to an embodiment of the present invention; Figure 4 This is a schematic diagram of the P-light / S-light transmittance variation curves corresponding to different grid depths (e.g., 100nm / 120nm / 140nm) in embodiments of the present invention. Figure 5 This is a schematic diagram of the extinction ratio variation curves corresponding to different grid depths (such as 100nm / 120nm / 140nm) in embodiments of the present invention. Detailed Implementation

[0023] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] A high extinction ratio nanowire grid polarization device includes: a substrate, which is quartz glass; a functional film layer disposed on the surface of the substrate, the functional film layer being a composite structure of a Ti transition layer and an Al polarization functional layer; and a grid core structure formed on the surface of the functional film layer. The core structural parameters of the wire grid include: period Line width ,depth and duty cycle ; Duty cycle This is the ratio of line width to period, i.e.: .

[0025] In the embodiments, the thickness range of the Ti transition layer of the functional film is 4 to 10 nm, and the thickness range of the Al polarization functional layer of the functional film is 100 nm to 200 nm.

[0026] In this embodiment, the optimal parameter combination for the wire grid core structure is: duty cycle The period is 0.5. 100–110 nm, depth The wavelength is 150–200 nm.

[0027] In this embodiment, the incident angle of the wire grid core structure is 0±20°, and the polarization is defined as: S-light ( ) perpendicular to the grid, P light ( () Parallel to the grid.

[0028] In another embodiment, based on borosilicate quartz and general float optical glass, high aluminosilicate glass and sapphire single crystal transparent substrates can be extended to achieve compatibility with only minor adjustments to the film adhesion pretreatment parameters.

[0029] With depth ,cycle Duty cycle To determine the simulation parameter range, conduct simulation experiments: Among them, the polarization optical path is as follows Figure 2 As shown, P-ray (parallel): polarization direction is parallel to the plane of incidence (the plane formed by the incident ray and the normal). S-ray (Senkrecht): polarization direction is perpendicular to the plane of incidence. like Figure 3 The figure shows the full-band spectrum of the nanowire grating polarization device prepared in this embodiment. The test wavelength range covers 400–1600 nm. The curve shows that the P-light transmittance of the device is maintained at the design level, while the S-light transmittance is significantly suppressed. The corresponding extinction ratio meets the requirements for high-end equipment. (See figure). Transmittance - That is, the transmittance of P light; Transmittance - That is, the transmittance of S-light; Reflectivity - That is, the reflectivity of P light; Reflectivity - , which is the reflectivity of S-rays.

[0030] like Figure 4 As shown, the P-light / S-light transmittance varies with different grid depths (e.g., 100nm / 120nm / 140nm). The curves show that within the grid depth range of 100–200nm, the transmittance is linearly correlated with the grid depth, verifying the rationality of the film thickness parameter window in the process of this invention.

[0031] like Figure 5 As shown, the extinction ratio varies with different grid depths (e.g., 100nm / 120nm / 140nm), and the extinction ratio is positively correlated with the grid depth.

[0032] like Figure 1 As shown, a method for fabricating a high extinction ratio nanowire grating polarization device includes: Step S1: Prepare a matching silicon-based hard mold, i.e., a quartz substrate.

[0033] In this embodiment, the fabrication process of the silicon-based hard mold is as follows: A first-generation hard mold with a depth of 50 nm was prepared by dry etching with mixed gases. or, By introducing a metal mask layer and etching the metal mask layer and the dielectric layer in two steps, a second-generation deep hard model with a depth of 150nm is prepared.

[0034] Step S2: Deposit a Ti transition layer and an Al polarization functional layer on a quartz substrate to form a composite functional film.

[0035] In this embodiment, the deposition adopts a magnetron sputtering scheme, and the film thickness and uniformity are controlled by adjusting the sputtering power, protective gas flow rate, cavity gas pressure and deposition time. or, The deposition process employed an electron beam evaporation method, sequentially depositing a Ti transition layer and an Al polarization layer. The thickness of the Ti transition layer ranged from 4 to 10 nm, while the thickness of the Al polarization layer ranged from 100 nm to 200 nm.

[0036] This invention offers two thin film deposition processes: magnetron sputtering and electron beam evaporation. Magnetron sputtering uses continuous deposition with dual targets to precisely control the thickness and uniformity of the Ti transition layer (4-10 nm) and the Al polarization layer (100-200 nm). Electron beam evaporation, on the other hand, achieves high-purity film deposition, meeting different precision and production capacity requirements while ensuring the compactness and performance stability of the functional film.

[0037] Step S3: Coat the composite functional film layer with pure organic nanoimprint adhesive and perform nanoimprinting using a quartz substrate to transfer the grid pattern.

[0038] In this embodiment, the pure organic nanoimprinting adhesive is the KSA08 series imprinting adhesive. The appropriate dilution ratio and spin coating speed are adopted according to the specifications of the hard mold, namely: For the first-generation hard mold, the printing adhesive dilution ratio is 1:4, the uniform spraying speed is 3000rpm, and the platform temperature is room temperature, achieving a near-no-base adhesive state. For the second-generation deep hard mold, the printing adhesive dilution ratio is 1:2, the uniform coating speed is 2000 rpm, the platform temperature is room temperature, and the printing pressure is in the low load range.

[0039] In another embodiment, when the target gate depth is between 50 and 150 nm or a special period / duty cycle is required, a new type of silicon hard mode is selected, which is adapted to gate structures with a period of 50 to 300 nm. For the new type of silicone hard mold, the printing adhesive dilution ratio is 1:3 to 1:3.5, the spin coating speed is 2500 to 3000 rpm, the platform temperature is room temperature, and the thickness of the base adhesive is precisely controlled.

[0040] This invention uses KSA08 series pure organic nano-imprinting adhesive. By adjusting the dilution ratio (1:2 to 1:4), the uniform coating speed (2000 to 3000 rpm), and the imprinting parameters, near-base adhesive-free molding is achieved, reducing the damage to the structure caused by subsequent adhesive removal processes. After imprinting, the grid line width and height dimensional deviations are small, and the structural consistency is significantly improved, solving problems such as hard mold adhesion and demolding breakage in traditional imprinting.

[0041] Step S4: Dry etching is performed on the imprinted Al polarization functional layer using a multi-component mixed gas to form a wire grid core structure.

[0042] In the embodiments, dry etching distinguishes between two working conditions: conventional deep etching and deep extended etching by adjusting the radio frequency power, bias voltage and reaction gas flow ratio, and matches the etching reaction time according to the target gate depth.

[0043] Step S5: Perform combined post-cleaning on the etched grid core structure to remove residual adhesive.

[0044] In this embodiment, the combined post-cleaning specifically includes: First, plasma oxidation treatment is performed, followed by constant-temperature immersion in a high-temperature organic alkaline solution, and finally immersion and cleaning in a polar organic solvent.

[0045] This invention designs and matches different etching times and gas ratios for grids with conventional depths (50nm) and large depths (100-200nm) to ensure the perpendicularity (85°-90°) and contour accuracy of the grid sidewalls. The combined plasma oxidation, high-temperature chemical immersion, and organic solvent post-cleaning thoroughly removes residual adhesive while avoiding structural damage such as grid wire breakage, adhesion, and wire breakage, thereby improving device yield.

[0046] Example: Using a standard WGP device (target cycle time) Line width ,depth For example: Using a self-developed second-generation silicon-based deep hard mold, the cycle... ,depth ; Quartz glass was selected as the substrate, with a thickness of 1mm; A composite film was continuously deposited by magnetron sputtering, with a 5 nm transition layer and a 150 nm aluminum polarization layer. Using KSA08 series pure organic printing adhesive, diluted at a ratio of 1:2, medium-low speed uniform coating, room temperature low load printing, to achieve near-base adhesive-free molding. A basic multi-component mixed gas etching process is employed, with a reaction time matched to the standard depth. Post-cleaning is performed using a multi-stage cleaning process consisting of plasma oxidation pretreatment, high-temperature chemical immersion, and organic solvent cleaning. The test results show that the measured grating period, linewidth, and depth under electron microscopy match the design values; the transmittance is stable across the entire wavelength range of 400–1600 nm, and the extinction ratio meets the specifications for high-end equipment.

[0047] Finally, it should be noted that the above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A high extinction ratio nanowire grating polarization device, characterized in that, include: The substrate is made of quartz glass. Functional film layer, which is disposed on the surface of the substrate, is a composite structure of Ti transition layer and Al polarization functional layer; A wire grid core structure is formed on the surface of the functional film layer; The core structural parameters of the wire grid include: period Line width ,depth and duty cycle ; Duty cycle This is the ratio of line width to period, i.e.: 。 2. The high extinction ratio nanowire grating polarization device according to claim 1, characterized in that, The thickness range of the Ti transition layer in the functional film is 4–10 nm, and the thickness range of the Al polarization functional layer in the functional film is 100 nm–200 nm.

3. The high extinction ratio nanowire grating polarization device according to claim 1, characterized in that, Duty cycle of the wire grid core structure The period is 0.

5. 100–110 nm, depth The wavelength is 150–200 nm.

4. The high extinction ratio nanowire grating polarization device according to claim 1, characterized in that, The incident angle of the wire grating core structure is 0±20°, and the polarization is defined as S-beam. Perpendicular to the grid, P-beam Parallel to the grid.

5. A method for fabricating a high extinction ratio nanowire grating polarization device, characterized in that, include: Step S1: Prepare a matching silicon-based hard mold, i.e., a quartz substrate; Step S2: Deposit a Ti transition layer and an Al polarization functional layer on a quartz substrate to form a composite functional film. Step S3: Coat the composite functional film layer with pure organic nanoimprint adhesive and perform nanoimprinting using a quartz substrate to transfer the grid pattern. Step S4: Dry etching is performed on the imprinted Al polarization functional layer using a multi-component mixed gas to form a wire grid core structure. Step S5: Perform combined post-cleaning on the etched grid core structure to remove residual adhesive.

6. The preparation method according to claim 5, characterized in that, In step S1, the fabrication process of the silicon-based hard mold is as follows: A first-generation hard mold with a depth of 50 nm was prepared by dry etching with mixed gases. or, By introducing a metal mask layer and etching the metal mask layer and the dielectric layer in two steps, a second-generation deep hard model with a depth of 150nm is prepared.

7. The preparation method according to claim 5, characterized in that, In step S2, the deposition adopts a magnetron sputtering scheme, and the film thickness and uniformity are controlled by adjusting the sputtering power, protective gas flow rate, cavity gas pressure and deposition time. or, The deposition process employed an electron beam evaporation method, sequentially depositing a Ti transition layer and an Al polarization layer. The thickness of the Ti transition layer ranged from 4 to 10 nm, while the thickness of the Al polarization layer ranged from 100 nm to 200 nm.

8. The preparation method according to claim 6, characterized in that, In step S3, the pure organic nano-imprinting adhesive is the KSA08 series imprinting adhesive. The appropriate dilution ratio and spin coating speed are adopted according to the specifications of the hard mold, namely: For the first-generation hard mold, the printing adhesive dilution ratio is 1:4, the uniform spraying speed is 3000rpm, and the platform temperature is room temperature, achieving a near-no-base adhesive state. For the second-generation deep hard mold, the printing adhesive dilution ratio is 1:2, the uniform coating speed is 2000 rpm, the platform temperature is room temperature, and the printing pressure is in the low load range.

9. The preparation method according to claim 5, characterized in that, In step S4, dry etching distinguishes between two working conditions: conventional deep etching and deep extended etching by adjusting the radio frequency power, bias voltage, and reaction gas flow ratio, and matches the etching reaction time according to the target gate depth.

10. The preparation method according to claim 5, characterized in that, In step S5, the combined post-cleaning specifically includes: First, plasma oxidation treatment is performed, followed by constant-temperature immersion in a high-temperature organic alkaline solution, and finally immersion and cleaning in a polar organic solvent.